Psychological Elitology as a Direction of PsychologicalThought - N B Кarabuschenko (Peoples' Friendship University of Russia (RUDN University), 2008)
The article proves the urgency of the development of a new direction in psychology - «psychological elitology», and also perspective ways of the research in the given field are submitted in the article.